ELASTICITIES OF OUTPUT SUPPLY AND INPUT DEMAND OF INDONESIAN FOODCROPS AND THEIR POLICY IMPLICATIONS: MULTI-INPUT MULTI-OUTPUT FRAMEWORK*) - SIREGAR, HERMANTO (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 2 Juli 2007, 2012)
ABSTRAK Ekonomi pertanian terbiasa melakukan analisisnya menggunakan pendekatan komoditas tunggal (output-tunggal, input-ganda). Masalahnya ialah pendekatan ini cenderung tidak sesuai dengan realitas di mana kebanyakan sistem produksi pertanian berkarakteristik output-ganda. Termotivasi oleh masalah ini, makalah ini ditulis dengan tujuan menjelaskan pendekatan input-ganda output-ganda (MI-MO) serta mengaplikasikannya pada subsektor tanaman pangan Indonesia. Berdasarkan pendekatan MI-MO selanjutnya dibangun sebuah model ekonometrika yang diestimasi dengan metode seemingly unrelated regression (SUR) terestriksi. Dugaan elastisitas harga silang yang diperoleh dari hasil estimasi model menunjukkan signifikannya efek silang harga input dan harga output terhadap permintaan input dan penawaran output. Hal ini menjustifikasi penggunaan pendekatan MI-MO pada subsektor tanaman pangan. Implikasi penting yang diperoleh dari studi ini ialah kebijakan harga, baik input maupun output, diperkirakan tidak efektif untuk diterapkan. Namun apabila secara politik kebijakan tersebut diperlukan, maka hendaklah diterapkan pada input karena besaran absolut elastisitas silang tersebut lebih besar pada permintaan input dibandingkan pada penawaran output. Kata kunci: Multi-Input Multi-Output, Tanaman Pangan, Seemingly Unrelated Regression, Elastisitas. ABSTRACT It is a commonly practiced that agricultural economists frame their analyses within the single commodity (multi-input single-output) framework. The problem with this framework is that this seems to be inappropriate because most agricultural production systems are characterized by multi-product farms. Motivated by this problem, this paper is aimed at providing a brief explanation on the multi-input multi-output (MI-MO) framework and applying the framework on the Indonesian food crops subsector. Based on this framework, an econometric model is specified and then estimated using the restricted seemingly unrelated regression method. Estimated cross-price elasticities obtained from the model suggest the significance of cross-effects of input or output prices on input demand or output supply, justifying the MI-MO nature of the crops. The most notable policy implication from this study is that a price policy on either outputs or inputs may not be effective. If, however, such a policy were politically desirable, it should be applied on inputs rather than on outputs because the magnitudes of the elasticities are in absolute term higher in input demands than in output supplies. Keywords: Multi-Input Multi-Output, Food Crops, Seemingly Unrelated Regression, Elasticities.
Keywords: Multi-Input Multi-Output, Tanaman Pangan, Seemingly Unrelated Regression, Elastisitas. (Multi-Input Multi-Output, Tanaman Pangan, Seemingly Unrelated Regression, Elastisitas)